2021
DOI: 10.1016/j.jnucmat.2021.153138
|View full text |Cite
|
Sign up to set email alerts
|

Spent nuclear fuel in dry storage conditions – current trends in fuel performance modeling

Abstract: The role of dry storage in spent nuclear fuel management becomes more and more important. Originally intended to serve as a temporary solution for a few decades until final disposal, now dry storage period is to be extended to 100 years and beyond. It has to be proven for licensing that the fuel rod integrity during dry storage is ensured. Since it is difficult to provide experimental support, the licensing process has to rely largely on numerical simulations. This paper reviews the literature associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 103 publications
0
2
0
1
Order By: Relevance
“…Since 2001, after 3-5 years of storing, they have been transferred to the spent-fuel dry storage facility (SFDSF) at the site, which can accommodate 9120 FAs in 380 ventilated storage casks of 144 t each. The SFDSF facility was designed for a 50-year storage lifetime, which is a period defined on the basis of the degradation and integrity reduction processes that may affect the fuel which is subjected to high temperature and high tensile stresses, e.g., hydrogen-related effects, creep, fission gas release, and fuel swelling [26,27]. Beyond this period, it would be necessary to provide sufficient evidence that the spent fuel condition would not have deteriorated to an extent that any handling or retrieval would be prevented.…”
Section: Snf Radioactivity Results and Discussionmentioning
confidence: 99%
“…Since 2001, after 3-5 years of storing, they have been transferred to the spent-fuel dry storage facility (SFDSF) at the site, which can accommodate 9120 FAs in 380 ventilated storage casks of 144 t each. The SFDSF facility was designed for a 50-year storage lifetime, which is a period defined on the basis of the degradation and integrity reduction processes that may affect the fuel which is subjected to high temperature and high tensile stresses, e.g., hydrogen-related effects, creep, fission gas release, and fuel swelling [26,27]. Beyond this period, it would be necessary to provide sufficient evidence that the spent fuel condition would not have deteriorated to an extent that any handling or retrieval would be prevented.…”
Section: Snf Radioactivity Results and Discussionmentioning
confidence: 99%
“…-The temperature evolution depends on fuel enrichment, burnup and cooling performance of the cask and lies in the [20°C, 300°C] range. It has been shown that there is a temperature gradient along the length of the fuel assembly (Hong et al, 2020;Feria and Herranz, 2011;Konarski et al, 2021) but not across the thickness (< 1°C) (EPRI, 2011). -Moreover, fuel assemblies are subjected to a pressure difference between the external and internal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…However, delays in the introduction of permanent geological disposal facilities and in governments' decisions about reprocessing processes have led to the need for storage systems for SNF other than spent fuel pools, which are reaching their maximum capacity. In this framework, dry cask systems have been proposed and accepted worldwide as an interim storage system for SNF for up to 100 years [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%